Advancing fishing technology education and research: a 65-year legacy at Nha Trang University, Vietnam - Khanh Quoc Nguyen; Phu Duc Tran; Phuong Viet Le; Luong Trong Nguyen; Phuong Van To (Journal of Fisheries)
As a coastal country, Vietnam relies on marine exploitation for food security and livelihoods. Training human resources to research, exploit, and manage marine resources is an important strategy to maintain rapid and sustainable economic growth and development. Official training in fishing technology at Nha Trang University (NTU) started in 1959. With 65 years of teaching, the unique program only offered at NTU, has made significant contribution to social-economic development in general and sustainable marine fisheries in particular. In this paper, we review the major achievements in teaching and scientific research in fishing technology at NTU as well as highlight the challenges and progress. Over the years, thousands of students have been trained under the fishing technology program and they then have worked all over the country, working in fisheries management, science, and services. Hundreds of research projects and peer-reviewed papers have been conducted and published. Those have supported fishing efficiency, environmentally friendly fishing methods, and effective management. However, the number of fishing technology students has decreased during the past few years because of unfavorable study and working environments where students are often exposed to commercial fishing vessels that frequently operate under rough weather conditions. Despite challenges and difficulties, NTU is determined to maintain the program to support the ocean economic development of the nation.